Conservation of the endangered Mediterranean tortoise Testudo hermanni hermanni: The contribution of population genetics and historical demography. (March 2016) - Zenboudji, Saliha; Cheylan, Marc; Arnal, Véronique; Bertolero, Albert; Leblois, Raphael; Astruc, Guillelme; Bertorelle, Giorgio; Pretus, Joan Ll.; Lo Valvo, Mario; Sotgiu, Giuseppe; Montgelard, Claudine
Abstract: Estimating the genetic variation and demographic trends of species in decline is of major concern in conservation genetics. This study contributes to understanding how historical and anthropogenic factors shape the distribution of current genetic diversity in one of the most endangered reptiles in Western Europe, the Hermann's tortoise Testudo hermanni hermanni. We used 17 microsatellite loci, chosen from a pyrosequencing library specifically developed for the subspecies to genotype eight populations distributed over about 30 sample localities covering almost the entire geographic distribution of the sub-species. The population genetic results reflect a very strong genetic structure and identify three major clusters among the Hermann's tortoise in the occidental Mediterranean basin: a continental cluster (Albera in Spain, Var in France and continental Italy), an insular cluster (Corsica, Sardinia and Sicily) and a cluster of mixed lineage (Minorca). Each of the eight studied populations is characterized by only one lineage except for Minorca, in which two lineages were identified. In contrast to what most empirical studies predict, the genetic diversity of the Hermann's tortoise is greater on islands than on the continent. Islands can therefore be considered as genetic sanctuaries with high conservation potential for this species, particularly in Corsica. Historical demographic patterns inferred with a generalized stepwise-mutation model (GSM) using maximum likelihood showed significant past demographic changes in only two of the eight sampled populations: a demographic bottleneck was detected in the Albera population (Spain) and a demographic expansion in Corsica (France). In contrast to what was argued in previous studies, these results indicate that the Hermann's tortoise lineage found in Corsica is autochthonous. The origin of both lineages found in Minorca remains speculative. Lastly, our study identifies the six most relevant management units (sensuMoritz, 1994 ) for conservation purposes on the basis that they represent a significant part of the evolutionary legacy of the species. Some conservation recommendations were proposed, in particular for the most threatened population in Albera.